Conhecimento em gestão estratégica na globalização neoliberal: uma análise crítica - Godoi, André Luis Bezerra Cavalcanti (2015)
This work contemplates the mismatch between the extraordinary expansion of the strategic management (SM) field and the rising critique to its incapacity to deal with the neoliberal globalization crises. The critical analisys begins showing how the universalization of americanism is followed by the universalization of management and strategic management. After that, explores how the neoliberal market and nonmarket discourses reproduce simplist discourses that contribute to legitimize the global actuation of the corporation. At last, it deals with the preference for the great modern corporation, marginalizing other organizational formats of relevance specially for emergent economies. The resulting integrative framework is then applied to a selection of SM scientific articles, that allowed the identification of five themes: geopolitics of knowledge, scientific empiricism, simplified conceptions of markets and institutions, corporative governance and capitalism. The exploration of the connection of SM knowledge and the neoliberal economic and geopolitic ordainment show how the field can have relevance to society, and also promotes the approximation of the mainstream with critical perpectives.